Răspuns :
Răspuns:
FeCl3 + 3NaOH → Fe(OH)3 + 3NaCl
Fe(OH)3 + 3NaCl → FeCl3 + 3NaOH
b) MNaOH=40+16+1=40g/mol
MFe(OH)3=56+3×16+3×1=107g/mol
3×40g........107g
FeCl3 + 3NaOH → Fe(OH)3 + 3NaCl
120g.........xg
x=120×107/3×40=107g Fe(OH)3
c) n=m/M=120/40=3moli NaOH
3moli...............................3moli
FeCl3 + 3NaOH → Fe(OH)3 + 3NaCl
3moli..............................ymoli
y=3×3/3=3 moli NaCl
Explicație:
Răspuns:
Explicație:
a) FeCl3+3NaOH=Fe(OH)3+3NaCl
b) 3*40 g 107g
120 g x
x=107 g
c)nNaOH=m/M=120g/40g/mol=3moli
3moli NaOH..........3moliNaCl
3moli y
y=3 moli